Front Cover: Allostery in Guest Binding of Rim‐to‐Rim‐Connected Homoditopic Biscavitands (Eur. J. Org. Chem. 20/2016). Issue 20 (18th July 2016) - Shimoyama, Daisuke; Yamada, Hitomi; Ikeda, Toshiaki; Sekiya, Ryo; Haino, Takeharu
Abstract : The cover picture shows the X‐ray crystal structure and the allosteric guest binding of a rim‐to‐rim connected phosphonate biscavitand. The biscavitand is bound to the cationic ammonium guests through hydrogen bonding and CH–π interactions, which demonstrates the positive allosteric effect. A single‐crystal X‐ray structure analysis of the biscavitand reveals that the two cavities of the biscavitand are tightly coupled. The positive allosteric effect is determined by the tightly connected cavities. The binding information of the first guest is transferred to the second cavity, which becomes preorganized. Details are discussed in the Communication by T. Haino et al. onp. 3300 ff .